Association of Clinical Signs of Occlusal Trauma with Gingival Recession among Patients Reporting to a Prosthodontic Department: A Cross-Sectional Study - Khalid Yaqub; Maryam Mumtaz; Hadia Imran Qureshi; Muhammad Raza; Asad Naeem Hafeez; Um E Habiba; Khezran Qamar; Sajid Naeem (Pakistan BioMedical Journal, 2026)
Gingival recession is a common dental problem with signs and symptoms of dentine hypersensitivity, root caries, and poor esthetics. Occlusal forces beyond the normal adaptive capacity of the periodontium can seriously affect the health of gingival tissues. Objectives: To determine the association between gingival recession and signs of trauma from occlusion such as dental fremitus, tooth migration, and tooth wear among the patients reported to the Department of Prosthodontics, LMDC, Lahore. Methods: A total of 150 patients of both genders, aged 30-70 years, were recruited. A single trained prosthodontist carried out the periodontal examination of the buccal anterior teeth. Patients were seated in the dental chair a thorough clinical examination was performed using a dental exam set to check the signs and symptoms of occlusal trauma and gingival recession. The following parameters were assessed: 1. plaque index, 2. supra/subgingival calculus/ 3. gingival recession, 4. Tooth wear facets; 5. fremitus. 6. Tooth migration. Results: Severe gingivitis was found in 32.0% of patients, and calculus was present in 58.7% of patients. 14.0% of patients had poor oral hygiene status. 51.3% of patients were found with gingival recession. Dental fremitus was present in 56.7% of patients; wear facets were present in 42.7% of patients; whereas tooth migration was found in 48.0% of patients. Conclusions: It was concluded that trauma from occlusion may be a significant risk factor for gingival recession. Patients with signs of trauma from occlusion should be monitored for gingival recession.